Local species: Methods of cultivation, some successes and some problems - Kalewar, Ram Ashraya Saha (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
Farmer's description of paddy species, methods of cultivation, and use.